KnowledgeBoat Logo

Mathematics

From the figure (2) given below, find the values of :

(i) tan x

(ii) cos y

(iii) cosec2 y - cot2 y

(iv) 5sin x+3sin y3 cot y\dfrac{5}{\text{sin x}} + \dfrac{3}{\text{sin y}} - 3\text{ cot y}.

From the figure, find the values of (i) tan x (ii) cos y (iii) cosec^2 y - cot^2 y. Trigonometrical Ratios, ML Aggarwal Understanding Mathematics Solutions ICSE Class 9.

Trigonometrical Ratios

48 Likes

Answer

From Figure,

BD = BC - CD = 21 - 5 = 16.

In right-angled ∆ACD,

By pythagoras theorem we get,

⇒ AC2 = AD2 + CD2

⇒ AD2 = AC2 - CD2

⇒ AD2 = (13)2 - (5)2

⇒ AD2 = 169 - 25

⇒ AD2 = 144

⇒ AD = 144\sqrt{144}

⇒ AD = 12.

In right-angled ∆ABD,

By pythagoras theorem we get,

⇒ AB2 = AD2 + BD2

⇒ AB2 = 122 + 162

⇒ AB2 = 144 + 256

⇒ AB2 = 400

⇒ AB = 400\sqrt{400}

⇒ AB = 20.

(i) In right-angled ∆ACD,

tan x = PerpendicularBase\dfrac{\text{Perpendicular}}{\text{Base}}

= CDAD=512\dfrac{CD}{AD} = \dfrac{5}{12}.

Hence, tan x = 512\dfrac{5}{12}.

(ii) In right-angled ∆ABD,

cos y = BaseHypotenuse\dfrac{\text{Base}}{\text{Hypotenuse}}

= BDAB=1620=45\dfrac{BD}{AB} = \dfrac{16}{20} = \dfrac{4}{5}.

Hence, cos y = 45\dfrac{4}{5}.

(iii) In right-angled ∆ABD,

cosec y = HypotenusePerpendicular\dfrac{\text{Hypotenuse}}{\text{Perpendicular}}

= ABAD=2012=53\dfrac{AB}{AD} = \dfrac{20}{12} = \dfrac{5}{3}.

cot y = BasePerpendicular\dfrac{\text{Base}}{\text{Perpendicular}}

= BDAD=1612=43\dfrac{BD}{AD} = \dfrac{16}{12} = \dfrac{4}{3}.

Substituting values in cosec2 y - cot2 y

=(53)2(43)2=259169=99=1.= \Big(\dfrac{5}{3}\Big)^2 - \Big(\dfrac{4}{3}\Big)^2 \\[1em] = \dfrac{25}{9} - \dfrac{16}{9} \\[1em] = \dfrac{9}{9} = 1.

Hence, cosec2 y - cot2 y = 1.

(iv) In right-angled ∆ACD,

sin x = PerpendicularHypotenuse\dfrac{\text{Perpendicular}}{\text{Hypotenuse}}

= CDAC=513\dfrac{CD}{AC} = \dfrac{5}{13}.

In right-angled ∆ABD,

sin y = PerpendicularHypotenuse\dfrac{\text{Perpendicular}}{\text{Hypotenuse}}

= ADAB=1220=35\dfrac{AD}{AB} = \dfrac{12}{20} = \dfrac{3}{5}.

Substituting values in 5sin x+3sin y3 cot y\dfrac{5}{\text{sin x}} + \dfrac{3}{\text{sin y}} - 3\text{ cot y}, we get :

=5513+3353×43=13+54=14.= \dfrac{5}{\dfrac{5}{13}} + \dfrac{3}{\dfrac{3}{5}} - 3 \times \dfrac{4}{3} \\[1em] = 13 + 5 - 4 \\[1em] = 14.

Hence, 5sin x+3sin y3 cot y=14\dfrac{5}{\text{sin x}} + \dfrac{3}{\text{sin y}} - 3\text{ cot y} = 14

Answered By

31 Likes


Related Questions